Practical Dermoscopy - Liu, Jie.; Zou, Xian-biao.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book aims to provide readers with practical information on the procedure of streamline skin disease recognition with the use of dermoscopy. The first three chapters are mainly focused on the basic knowledge of dermoscopy, such as its history, how it works, the terminology. In the following chapters, the clinical photographs, dermoscopic images and histopathologic images of benign melanocytic neoplasms, malignant melanoma, basal cell carcinoma, seborrheic keratosis and related diseases, vascular diseases, squamous cell neoplasms and other neoplasms are presented in a case-based format. The clinical characteristics are introduced briefly, and the dermoscopic features are highlighted with a number of pictures. The chapter 12 to chapter 14 introduce the dermoscopic appearance of inflammatory skin diseases, infectious and parasitic skin diseases, hair and nail diseases, respectively, which is the extended application of dermoscopy. Last but not least, the development and future of articifial intellegence assisted diagnosis based on dermoscopic images is introduced. Written by dermatologists who have been involved in dermoscopic diagnosis for a long time, this case-based book will be a valuable reference for dermatologists and those who are interested in related field.
Introduction of Dermoscopy -- Terminology in Dermoscopy -- Devices in Dermoscopy -- Diagnostic Strategies and Algorithms of Dermoscopy -- Benign Melanosytic Neoplasms -- Malignant Melanoma -- Basal Cell Carcinoma -- Seborrheic Keratosis and Related Diseases -- Vascular Diseases -- Squamous Cell Neoplasms -- Other Neoplasms -- Inflammatory Skin Diseases -- Infectious and Parasitic Skin Diseases -- Hair and Nail Diseases -- Artificial Intelligent Applications in Dermoscopy.
Keywords: Dermatology; Dermatology; Dermoscopy